TEF30 Interacts with Photosystem II Monomers and Is Involved in the Repair of Photodamaged Photosystem II in Chlamydomonas reinhardtii . Issue 2 (7th December 2015) - Muranaka, Ligia Segatto; Rütgers, Mark; Bujaldon, Sandrine; Heublein, Anja; Geimer, Stefan; Wollman, Francis-André; Schroda, Michael
Abstract : A protein conserved in the green cell lineage binds quantitatively to PSII monomers at the stromal side of thylakoid membranes and facilitates supercomplex assembly during PSII repair. Abstract: The remarkable capability of photosystem II (PSII) to oxidize water comes along with its vulnerability to oxidative damage. Accordingly, organisms harboring PSII have developed strategies to protect PSII from oxidative damage and to repair damaged PSII. Here, we report on the characterization of the THYLAKOID ENRICHED FRACTION30 (TEF30) protein in Chlamydomonas reinhardtii, which is conserved in the green lineage and induced by high light. Fractionation studies revealed that TEF30 is associated with the stromal side of thylakoid membranes. By using blue native/Deriphat-polyacrylamide gel electrophoresis, sucrose density gradients, and isolated PSII particles, we found TEF30 to quantitatively interact with monomeric PSII complexes. Electron microscopy images revealed significantly reduced thylakoid membrane stacking in TEF30-underexpressing cells when compared with control cells. Biophysical and immunological data point to an impaired PSII repair cycle in TEF30-underexpressing cells and a reduced ability to form PSII supercomplexes after high-light exposure. Taken together, our data suggest potential roles for TEF30 in facilitating the incorporation of a new D1 protein and/or the reintegration of CP43 into repaired PSII monomers, protecting repaired PSII monomers from undergoing repeated repair cycles or facilitating the migration of repaired PSII monomers back to stacked regions for supercomplex reassembly.